Peran Kepemimpinan Sekolah dalam Meningkatkan Hasil Belajar Anak Berkebutuhan Khusus di Sekolah Terintegritas - Windy Rahmadani; Siska Prasinta Kesuma; Opi Andriani (Education : Jurnal Sosial Humaniora dan Pendidikan, 2024)
The aim of this research is to determine the role of school leadership in improving the learning outcomes of children with special needs in integrated schools. The method used in this research is descriptive with a qualitative approach. Data collection techniques include: observation, interviews, and documentation. The research subjects or informants were school principals and teachers. The results of interviews conducted by the author with the leadership of SDN 23/VI Rantau Panjang I show that regarding children with special needs at this school, the leadership and parents work together in guiding children so that the achievements of children with special needs can be on par with normal children.